PELAKSANAAN PERJANJIAN PT.MIR (MAJU INDO RAYA) - Abdi Novia; Syafri Gunawan; Dermina Dalimunthe (Jurnal El-Thawalib, 2021)
The purpose this study to implementation of the agreement between PT.MIR (MAJU INDO RAYA) and ampolu village community. This research is emprical Field Researeh. With data collection techniquedone by interview and observation. Data were analyzed using qualitative approach method. The result of the research shows that the  implementation of the agreement between PT.MIR (MAJU INDO RAYA) and ampolu village community.  Not in accordance with what  was promised as well as violating the agreement that has been made by PT.MIR (MAJU INDO RAYA). Where  PT.MIR (MAJU INDO RAYA) does   not water the road three  times a  day,  PT.MIR (MAJU INDO RAYA)  does not fill  the road with sertu and  pare maintenance isnotcarried out.